High‐Efficiency Monolithic Photosupercapacitors: Smart Integration of a Perovskite Solar Cell with a Mesoporous Carbon Double‐Layer Capacitor. Issue 11 (14th September 2021) - Berestok, Taisiia; Diestel, Christian; Ortlieb, Niklas; Buettner, Jan; Matthews, Joel; Schulze, Patricia S. C.; Goldschmidt, Jan Christoph; Glunz, Stefan W.; Fischer, Anna
Abstract : The integration of solar cells with supercapacitors into hybrid monolithic power packs can provide energy autonomy to smart electronic devices of the Internet of Things (IoT) by mediating between intermittent load and supply. Herein, such a photorechargeable supercapacitor (also called a photosupercapacitor) is developed via a three‐electrode integration of a p–i–n halide perovskite solar cell with a gel electrolyte‐type supercapacitor that uses mesoporous N‐doped carbon nanospheres (MPNC) as the active electrode material. Benefiting from the large surface area, well‐defined mesoporous structure, and homogeneous particle size of the MPNC material, the supercapacitor demonstrates high capacitance, resulting in large energy and power densities with a high charge/discharge efficiency. Its integration with a large‐area (1 cm 2 ) FA0.75 Cs0.25 Pb(I0.8 Br0.2 )3 perovskite solar cell, with an optimized layer sequence to minimize degradation, results in a photosupercapacitor exhibiting fast (< 5 s) photocharging up to 1 V. The outstanding peak overall photoelectrochemical energy conversion efficiency of 11.5% is a result of a high solar cell power conversion efficiency of 12.5%, a high supercapacitor storage efficiency of 92%, and low internal energy losses due to monolithic integration. These results underline the high potential of this type of device toward application in the IoT. Abstract : A novel approach for the fabrication of a monolithic photorechargeable supercapacitor with 11.5% efficiency is demonstrated. The three‐electrode device comprises a p–i–n halide perovskite solar cell, smartly integrated with a mesoporous carbon‐based double‐layer capacitor. It attains simultaneous solar energy harvesting, conversion, storage, and on‐demand release, showing the capability to mediate between intermittent supply and demand toward energy‐autonomous devices.